The Relevance of Maqasid Syari'ah Yusuf Qardawi to the Dropshipping Concept - Imam Kamaluddin; Hannan Arsyad Karimullah (al-Afkar, Journal For Islamic Studies, 2026)
Dropshipping is a growing digital business model in e-commerce. However, from an Islamic economic perspective, this system creates legal dilemmas related to product ownership and contract transparency. This study aims to analyze the relevance of Yusuf Al-Qaradawi's maqashid sharia to the dropshipping concept to determine whether this business model complies with Islamic economic principles. The research method used is a qualitative approach based on literature review, with deductive and comparative analysis of maqashid sharia. The results show that dropshipping can be implemented in Islamic economics, provided there is clarity in the contract, transparency of information, and protection of consumer rights to avoid gharar. Therefore, clearer sharia regulations are needed for dropshipping practices to ensure compliance with maqashid sharia.